Respect Minority and Community Rights in Any Health Care Reforms - The English Speaking Catholic Council (ESCC) (2004)

Gardez le lien avec la communauté - The English Speaking Catholic Council (ESCC) (2004)

Mémoire présenté par le Conseil catholique d’expression anglaise sur les conditions de vie des aînés - The English Speaking Catholic Council (ESCC) (2007)

Public Consultation on Seniors' Living Conditions : A Social Issue That is the Responsibility of Us All Quebecers - The English Speaking Catholic Council (ESCC) (2007)
The English Speaking Catholic Council would like to congratulate the Government of Quebec for recognizing the importance of issues related to seniors and an aging population and its establishment of the post of Minister Responsible for Seniors. We also welcome the initiative of Mme Marguerite Blais, the Minister Responsible for Seniors, to hold public hearings on seniors’ living conditions in Quebec, an issue on which our community and its institutions serving the elderly have considerable experience and great concern.